Comparison of the Effect of Macroeconomic Variables on the Sharia Shares Index in Indonesia, Malaysia, and Turkey - Taufik Nugroho (Ekonomi Islam Indonesia, 2020)
The purpose of this study was to analyze the efficiency of local government expenditure based on Islamic Human Development Index (I-HDI) in Local Government at the Indonesian’s Province using Data Envelopment Analysis (DEA). DEA is a non parametic method that was developed to measure the level of efficiency compared to the Decision Making Unit (DMU). This method can measure the efficiency of a government entity by using multi-input and multi-output. DEA result also can be used to identify wich input or output must be increased by Decision Making Unit (DMU) to reach optimum efficiency. The result from this study showed that the average of efficiency score in local government at Indonesian’s Province is increasing from 2015 until 2018. This study also indicates that North Sumatera, East Java, and Yogyakarta’s government spending were efficient in 4 years. While Bangka Belitung and West Papua achieve the lowest efficiency score, and should optimize input and increase the number of output to improve the efficiency. Morever, the main source of inefficiency is in Life birth rate indicators.